Bond behavior of coral aggregate concrete and corroded Cr alloy steel bar. (1st December 2022) - Sun, Zhen; Niu, Ditao; Wang, Xiaoqian; Zhang, Lu; Luo, Daming
Abstract: In the extremely hot and humid marine environment in the South China Sea, the application of Cr alloy steel bars and coral aggregate concrete (CAC) overcomes the problems of low durability of ordinary reinforced concrete structures and lack of construction materials, accelerates the construction of reefs. The bond-slip performance between CAC and Cr alloy steel bars is the basis of their cooperative work. Considering the complex composition of the microstructure and the structure of the interface of CAC, and the excellent corrosion resistance of Cr alloy steel bars, the bond properties between Cr alloy steel bars and CAC are different from those of ordinary reinforced concrete. Therefore, in this study, the influence of the corrosion ratio of the Cr alloy steel bar was considered, the corrosion of steel bars was accelerated via electricity, and a pull test was conducted to study the bond-slip constitutive relationship between the corroded Cr alloy steel bar and CAC. Through experimental research and theoretical analysis, the distribution law of the bond stress and slip value between the Cr alloy steel bar and CAC along the anchorage length was obtained under different corrosion ratios. The transfer mechanism of the bond stress and the difference in the bond anchorage position between the Cr alloy steel bar and CAC before and after corrosion were analyzed. A bond anchorage position function model reflecting the actual bond distribution law under different corrosion ratios was proposed and the bond-slip constitutive model was established, providing a reference for island construction in the South China Sea. Graphical abstract: Image 1 Highlights: The influence of corrosion ratio on the bond strength of Cr-alloy-reinforced coral aggregate concrete was studied. The differences in the bond stress-relative slip curves under different corrosion ratios were analyzed. A bond anchorage position function model under different corrosion ratios was proposed. The bond-slip constitutive relationship under different corrosion ratios was established.